2018
DOI: 10.1007/s00256-018-3040-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of patellotrochlear index in patellar height assessment on MRI—correction for variation due to change in knee flexion

Abstract: This study demonstrates high inter-observer correlation of PTI on MRI and high test-retest reliability indicating unconscious quadriceps contraction does not change the index sufficiently. Knee flexion significantly alters PTI, increased patellotrochlear engagement with flexion increases the index. We propose use of the formula cPTI = PTI -1.3a to correct the index to 0 degree knee flexion in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…In humans, a proximally positioned patella (patella alta) is associated with patellar instability, due to which the patella exceeds the femoral trochlea proximally and loses support from the trochlear ridge [11,[14][15][16]. Based on these human studies, veterinary researchers have investigated the association between the PLL/PL and patellar luxation [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a proximally positioned patella (patella alta) is associated with patellar instability, due to which the patella exceeds the femoral trochlea proximally and loses support from the trochlear ridge [11,[14][15][16]. Based on these human studies, veterinary researchers have investigated the association between the PLL/PL and patellar luxation [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ahmad et al reported PTI values for 64 symptomatic patients, but they had only three healthy volunteers. 20 Thus, this current study represents an important addition to the literature providing a reference level of 36.8% for patella height as defined by PTI in a normal knee. It also suggests that PTI measurement has a good interclass correlation and excellent intraclass correlation.…”
Section: Discussionmentioning
confidence: 88%
“…B. patellotrochleärer Index) hat. Formeln zur Adaptation werden vorgeschlagen, können jedoch nur limitiert eine Aussage über die tatsächlich vorliegende Dynamik treffen [2].…”
Section: Funktionsabhängige äNderungen Der Statischen Parameterunclassified